Microbiomes of Antarctic pearlwort (Colobanthus quitensis) of the maritime Antarctic: distinct diversity and core microbes in rhizosphere and endosphere compartments of the plant - Yerkhova, A.; Parnikoza, I.; Pavlovska, M.; Yevchun, H.; Prekrasna-Kviatkovska, Y. (Ukrainian Antarctic Journal, 2022)
Plant microbiome plays a crucial role in the plants’ performance and fitness to the environment. The latter is especially significant for the plants withstanding the unfavorable conditions of the Antarctic. The study aimed to evaluate the microbiome of Antarctic pearlwort Colobanthus quitensis (Kunth) Bartl. growing in the wide range from the South Shetland Islands in the North to Marguerite Bay in the South (63°S – 68°S) in the maritime Antarctic. The composition of C. quitensis microbiome (rhizosphere and endophytes of the plant’s aerial part) was studied by 16S rRNA amplicon metagenomic sequencing on Illumina Novaseq 6000. The number of operational taxonomic units and diversity indices (Shannon, Simpson, Faith PD) of the endosphere microbiomes were lower (p < 0.05) than in the rhizosphere microbiomes, and the ANOSIM test revealed a difference (R = 0.9, p = 0.0001) in the microbiomes’ taxonomic structure. The diversity of the barren’s microbiome was lower compared to the rhizospheres’. Proteobacteria, Acidobacteria, Actinobacteria, Bacteroidota, Chloroflexi, and Verrucomicrobia were dominant in the rhizosphere. Similar phyla were found in the barren, yet the ratio of Actinobacteria was higher. Proteobacteria dominated in the endosphere, followed by Firmicutes, Actinobacteria, and Bacteroidota. Alphaproteobacteria, Actinobacteria, and Acidobacteria represented a large proportion of the core microbiota of C. quitensis rhizosphere. The endophyte microbiome’s core was mainly composed of Alphaproteobacteria, Gammaproteobacteria, and Firmicutes. On the family taxonomic level, Rhodobacteraceae, Microbacteriaceae, Rhizobiaceae, Xanthobacteraceae, Sphingomonadaceae, Comamonadaceae, Pseudomonadaceae, and Oxalobacteraceae were determined as the core for rhizosphere and endosphere. The correlation was low (R = 0.22, p = 0.04) between the rhizosphere microbiome composition and the latitude. Nevertheless, differential abundance of some bacterial taxa in the rhizosphere was attributed to the region of the plant’s growth: Northern, Central, or Southern part of the maritime Antarctic. The shift in the composition of microbial communities can be associated with the changing of the climatic conditions southwards along the Western coast of the Antarctic Peninsula.